2013
DOI: 10.1088/0256-307x/30/2/026102
|View full text |Cite
|
Sign up to set email alerts
|

A Single Cluster Covering for Dodecagonal Quasiperiodic Ship Tiling

Abstract: Single cluster covering approach provides a plausible mechanism for the formation and stability of octagonal and decagonal quasiperiodic structures. For dodecagonal quasiperiodic pattern such a single cluster covering scheme is still unavailable. Here we demonstrated that the ship tiling, one of the dodecagonal quasiperioidic structures, can be constructed from one single prototile with matching rules. A deflation procedure is devised by assigning proper orientations to the tiles present in the ship tiling inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…5a. A closely related covering by a single type of dodecagonal patch has been recently proposed by Liao with coworkers [27]; our shield tile always resolves into a square, a pair of triangles and a thin rhombus tile in their model. The possibility of single-cluster covering using the dodecagon patch in Fig.…”
Section: Geometrical Characteristics Of the Dodecagonal Quasicrystalmentioning
confidence: 75%
“…5a. A closely related covering by a single type of dodecagonal patch has been recently proposed by Liao with coworkers [27]; our shield tile always resolves into a square, a pair of triangles and a thin rhombus tile in their model. The possibility of single-cluster covering using the dodecagon patch in Fig.…”
Section: Geometrical Characteristics Of the Dodecagonal Quasicrystalmentioning
confidence: 75%
“…This fact has been noticed and extensively studied by Strang 14 15 and Richert 16 . In studying the 1D incommensurate structures, we found that the function y = sin(2 πμ n), where is the platinum number which is related to the dodecagonal quasiperiodic structure 8 11 12 13 , reveals an interesting picture as illustrated in Fig. 2a .…”
Section: Resultsmentioning
confidence: 99%
“…   is the platinum number which is related to the dodecagonal quasiperiodic structure [8,[11][12][13], reveals an interesting picture as illustrated in Fig.2a. In the boundary regions defined by y 1   , the graph seems folding together, reminding us of Escher's paintings based on the concept of Poincaré disc.…”
Section: Iia Directional Scaling Symmetry In Equilateral Triangular mentioning
confidence: 99%
See 2 more Smart Citations